2019
DOI: 10.18438/eblip29624
|View full text |Cite
|
Sign up to set email alerts
|

Local Users, Consortial Providers: Seeking Points of Dissatisfaction with a Collaborative Virtual Reference Service

Abstract: Abstract Objective – Researchers at an academic library consortium examined whether the service model, staffing choices, and policies of its chat reference service were associated with user dissatisfaction, aiming to identify areas where the collaboration is successful and areas which could be improved. Methods – The researchers examined transcripts, metadata, and survey results from 473 chat interactions originating from 13 universities between June and December 2016. Transcripts were coded for us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…a student or library staff member seeking assistance from a librarian) prior to returning to the user with an answer, demonstrating a collaborative approach to chat (Smith et al , 2016). In some more uncommon instances, such as library consortia, chat operators from outside the library respond to users' questions effectively, too; chat transcripts reviewed in this study indicated that users were only dissatisfied with the service they received after the chat operator revealed that they were from outside the library–not necessarily from the quality of the help they received (Barrett and Pagotto, 2019). And, with consortia, the chat service needs to be assessed from the perspective of all member libraries (Barrett and Greenberg, 2018).…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…a student or library staff member seeking assistance from a librarian) prior to returning to the user with an answer, demonstrating a collaborative approach to chat (Smith et al , 2016). In some more uncommon instances, such as library consortia, chat operators from outside the library respond to users' questions effectively, too; chat transcripts reviewed in this study indicated that users were only dissatisfied with the service they received after the chat operator revealed that they were from outside the library–not necessarily from the quality of the help they received (Barrett and Pagotto, 2019). And, with consortia, the chat service needs to be assessed from the perspective of all member libraries (Barrett and Greenberg, 2018).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Service quality is often a primary concern with chat reference (Barrett and Pagotto, 2019). Determining a plan for training chat operators (whether operators are librarians, library staff, or students) and scheduling chat services – towards a goal of providing consistent service – often proves difficult (Shepherd and Korber, 2014; Yang and Dalal, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The local librarians received higher satisfaction scores than external librarians overall, but the satisfaction scores of external librarians rose over time in certain categories, indicating that non-local librarians' performance improves as familiarity with other library locations grows. Barrett and Pagotto (2019) also compared chat service provided by "home" staff and operators from partner libraries in the area, but their research concerned user dissatisfaction. They found no significant difference in user dissatisfaction when patrons are served by local chat operators compared to partner chat operators.…”
Section: User Perceptions Of Chat Reference Staffing Modelsmentioning
confidence: 99%
“…In their article, Mawhinney & Kochkina (2019) presented the results of a study on virtual reference service, where they seek to determine whether or not the texting service is filling a different information need than chat and email by examining the level of difficulty and the topic of questions using these different methods of communication. Barrett & Pagotto (2019) examined whether the service model, staffing choices, and policies of its chat reference service were associated with user dissatisfaction, aiming to identify areas where the collaboration is successful and areas which could be improved. In their article chapter Cleveland & Philbrick (2018) provide an overview of virtual reference services, discuss key issues related to the provision of virtual reference services, review the literature on virtual reference services in academic health sciences libraries, and present a study on the trends in virtual reference services in academic health sciences libraries.…”
Section: Literature Reviewmentioning
confidence: 99%